Exploring students’ motives for studying psychology: a qualitative study - Mudhovozi, Pilot; Maree, Kobus (South African Journal of Higher Education, 2016)
The present study explored participants’ motives for studying psychology. A qualitative, exploratory, descriptive and contextual research design was used. The research method consisted of a brief survey. Four Black participants (male = 2; female = 2) for the study were purposefully selected from a Historically Black institution of higher learning in South Africa. The data collected through audio-taped individual, semi-structured interviews were analyzed by means of content analysis. The participants were asked to describe their motives for choosing psychology as a field of study. The results suggest that the participants chose psychology for various reasons. Minor gender differences were noted in the motives for the choice of psychology as a career. Further research on the topic is needed.